2009
DOI: 10.1109/tvcg.2009.112
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Interface for Interactive Exploration of DTI Fibers

Abstract: Abstract-Visual exploration is essential to the visualization and analysis of densely sampled 3D DTI fibers in biological speciments, due to the high geometric, spatial, and anatomical complexity of fiber tracts. Previous methods for DTI fiber visualization use zooming, color-mapping, selection, and abstraction to deliver the characteristics of the fibers. However, these schemes mainly focus on the optimization of visualization in the 3D space where cluttering and occlusion make grasping even a few thousand fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(11 citation statements)
references
References 24 publications
0
9
0
2
Order By: Relevance
“…While FA is among the most commonly found metrics of white matter structure in DTI studies, Koraonkar and coworkers (Korgaonkar, Cooper et al 2012) found through independent components analysis that fiber length has a predictive accuracy of 83% when measured in major depressive disorder vs. control subjects. Furthermore, because of its crucial role in fiber-tracking algorithms and its correlation to other metrics, fiber length is considered a valuable metric for assessing the accuracy of tractography protocols (Andreisek, White et al 2009; Chen, Ding et al 2009; Colby, Soderberg et al 2012; Kristo, Leemans et al 2012). Moreover, our use of multivariate analysis was conducted in order to specifically account for such covariance and improve on the ability to detect differences between groups.…”
Section: Discussionmentioning
confidence: 99%
“…While FA is among the most commonly found metrics of white matter structure in DTI studies, Koraonkar and coworkers (Korgaonkar, Cooper et al 2012) found through independent components analysis that fiber length has a predictive accuracy of 83% when measured in major depressive disorder vs. control subjects. Furthermore, because of its crucial role in fiber-tracking algorithms and its correlation to other metrics, fiber length is considered a valuable metric for assessing the accuracy of tractography protocols (Andreisek, White et al 2009; Chen, Ding et al 2009; Colby, Soderberg et al 2012; Kristo, Leemans et al 2012). Moreover, our use of multivariate analysis was conducted in order to specifically account for such covariance and improve on the ability to detect differences between groups.…”
Section: Discussionmentioning
confidence: 99%
“…Other examples for geometric abstractions are subway networks ( Fig. 1) and the contraction-based abstraction of brain connectivity [21], [22], [32] (Fig. 7).…”
Section: Axes Of Abstractionmentioning
confidence: 99%
“…Visual abstraction operators, on the other hand, strongly rely on cognition and need to be learned, similar to arbitrary symbols. 21 In addition to this connection to cognition and perception, several additional links to other fields that discuss abstraction can be made. Refinement in computing, for instance, is a concept that uses a verifiable transformation from an abstract program specification to a specific form that can then be executed.…”
Section: Constructing An Overarching Theorymentioning
confidence: 99%
“…However, in [47], [48] GPUs were used only for visualising tractography results. The approaches proposed in [49][51] perform deterministic tractography rather than dealing with a probabilistic Bayesian inference framework, as in our study.…”
Section: Discussionmentioning
confidence: 99%